2017
DOI: 10.1093/qjmed/hcx243
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 L412F polymorphism promotes a persistent clinical phenotype in pulmonary sarcoidosis

Abstract: This study identifies defective TLR3 function as a previously unidentified factor in persistent clinical disease in pulmonary sarcoidosis and reveals TLR3 L412F as a candidate biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Sarcoidosis is an inflammatory disease characterized by granulomatosis present in multiple organs and triggered by environmental factors that interact with environmental triggers to result in the innate immune activation of macrophages and dendritic cells, which further upregulates the expression of the major histocompatibility complex (MHC) and cytokines that induce the activation of the adaptive immune response ( 3 ). Previous GWAS on the sporadic and familial aggregation of sarcoidosis patients showed that the candidate genes are strongly associated with disease severity, including HLA and non-HLA genes ( 9 , 12 ). Most of the genes were related to T-cell regulation and T-cell activation during antigen presentation by APCs (antigen-presenting cells) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcoidosis is an inflammatory disease characterized by granulomatosis present in multiple organs and triggered by environmental factors that interact with environmental triggers to result in the innate immune activation of macrophages and dendritic cells, which further upregulates the expression of the major histocompatibility complex (MHC) and cytokines that induce the activation of the adaptive immune response ( 3 ). Previous GWAS on the sporadic and familial aggregation of sarcoidosis patients showed that the candidate genes are strongly associated with disease severity, including HLA and non-HLA genes ( 9 , 12 ). Most of the genes were related to T-cell regulation and T-cell activation during antigen presentation by APCs (antigen-presenting cells) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that class II HLA-DRB1*03:01 is associated with resolving disease more than the persistent group in Finnish, Croatia, and Czech sarcoidosis patients ( 9 11 ). Other non-HLA gene polymorphisms associated with clinical course, including TLR3 (L412F, rs3775291), promoted a persistent clinical phenotype in Irish and American Caucasian patients ( 12 ); also, tumor necrosis factor-β (TNF-β) alleles TNF-β1 and TNF-β3 were found to be associated with prolonged clinical course in Japan and Dutch sarcoidosis patients, respectively ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, consequences of this mutation on immune responses in primary human PUUV infection should require further studies [ 37 ]. The TLR3 p.L412F variant without enrichment in our patient population was observed in another two patients; this common variant exhibit neutral functional testing and it is not associated with any disease condition in heterozygous form [ 27 30 ]. All cases and their family members with the hypormophic TLR3 p.L742F variant or the common p.L412F variant were positive for HSV1 antibodies; none of them had a history of HSE.…”
Section: Discussionmentioning
confidence: 99%
“…We chose not to analyze activity of the TLR3 p.L412F variation, as this variant is not enriched in our patients and it is thoroughly analyzed by previously studies in different conditions. [27][28][29][30][31]…”
Section: The L742f Tlr3 Protein Is Severely Hypomorphic In Vitromentioning
confidence: 99%
“…Defects in the immune system, when dealing with lung microbiome, may be key drivers for ILDs development. Mutation of the innate sensor TLR3, which recognizes viral dsRNA, is associated with IPF and pulmonary sarcoidosis (30,31). Staphylococcus nepalensis released corisin, a peptide conserved in diverse staphylococci, induces apoptosis of lung epithelial cells and is upregulated in IPF patients with acute exacerbation compared to patients without disease exacerbation (32).…”
Section: Persistent Infections Are Associated With Ilds Developmentmentioning
confidence: 99%